ILMU HUKUM DAN PERKEMBANGANYA (KAJIAN KHUSUS HUKUM NORMATIF) - Imam Mahdi (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2016)
The main aim in this paper  is to determine the specificity of the nature  of the science of law (being suigeneris) and  the  development of the  jurisprudence of the  various  schools  that  dominate the  priodesasi the development of science in general.  Besides,  it is also about  schools  posistisme studied law which  is still to be  the  center of various  legal studies, although these schools  has  been criticized  by experts, especially after  the  emergence of the  theory  of relativity sebagaiman effect  on  natural  sciences (exact). Indonesia actually  embrace pluralism  in the  law, but in practice dominated by the  understanding of legal positivism. This understanding on the one hand  a major contribution to the establishment of law in Indonesia, especially in relation  to the legal hierarchy.  In another section of this paper  provides  a practical overview  of normative law as a form of research with various ragaan  easily understood. It mainly deals with issues  or legal problems that should  be put forward  by the applicant in determining the design  of the studies law